Socioeconomic and intellectual property analysis in pharmaceutical natural products - Madrigal Redondo, German (2018)
The absence of a consolidated definition of the term “natural product” is a problem to establish a relationship between this concept and intellectual property. The intellectual property includes many different categories, such as distinctive signs, invention patents, author rights, plant variety rights and other categories not recognize by all entities and countries denominated sui generis, for example, test data, traditional knowledge and the access to genetic and biologic resources. The objective of this study is to analyze with a diagnostic approach the added value that natural products have received through different types of intellectual property. Methods: The present study is a diagnostic and descriptive analysis of the relationships between natural products and the different types of intellectual property. A search using the World Health Organizations databases about intellectual property and the web pages of the world most important offices of intellectual property was used. Finally, a triangulation of the consulted information was carried out. Results and Conclusions: An increase of protected natural products was detected. The intellectual property identified categories were invention patents, plant variety rights, and distinctive signs. It is in consequence to the increase in national laws related to intellectual property that responds to the trades treaties present in some regions, for example, Latin America. However, there are two phenomena related to natural products. In first place, the natural products with some type of protection are concentrated in developed countries and multinational corporations, and in second place, a lot of natural products in Latin America do not have intellectual protection, usually due to the absence of the most beneficial categories of intellectual protection in the trades treaties or because these categories are not recognized by the States or international organizations.